Health education decreases incidence of hand eczema in metal work apprentices: Results of a controlled intervention study. (18th March 2020) - Reich, Anna; Wilke, Annika; Gediga, Günther; Baurecht, Hansjörg; Rodríguez, Elke; Jakasa, Ivone; Geier, Johannes; Mempel, Martin; Buhl, Timo; Weidinger, Stephan; Kezic, Sanja; John, Swen M.; et al.
Abstract: Background: Metal work apprentices (MWAs) frequently develop work‐related hand eczema (HE). Objectives: To evaluate the effect of health education on incidence of work‐related HE in MWAs and to assess confounding factors. Materials/methods: In a prospective controlled intervention study, 131 MWAs received educational training on prevention of HE, whereas 172 MWAs and 118 office work apprentices served as controls. At baseline and during three yearly follow‐ups, questionnaires were completed and hands were examined. Saliva samples were collected for assessment of filaggrin ( FLG ) null mutations and an explorative genome‐wide association study (GWAS), and levels of various cytokines were assessed from stratum corneum samples. Results: The 2‐year and 3‐year incidence of HE in the metalwork control group was 20.9% and 32.6%, respectively, which was significantly higher than in the intervention group (odds ratio [OR] 2.63, 95% confidence interval [CI] 1.31 to 5.28, P < .01 and OR 3.47, 95% CI 1.88 to 6.40, P < .0001). The knowledge score was higher in unaffected MWAs ( P < .05). Other factors significantly associated with developing HE in MWAs were smoking cigarettes ( P < .01) and FLG mutations ( P < .001). No significant associations were found regarding epidermal cytokine levels and GWAS. Conclusions: Health education is effective in primary prevention of HE in MWAs. Individual factors should be considered in targeted counseling.